Development of a Web-Based SQL Query Online Examination System with Automated Grading Using the MVC Design Pattern - Yunhasnawa, Yoppy; Windawati, Atif; Cinderatama, Toga Aldila; Vista, Candra Bella; Abdullah, Moch. Zawaruddin (Lembaga Komunitas Informasi Teknologi Aceh (KITA), 2024)
In this study, the Researchers provide the design, development, and evaluation of a web-based SQL exam system that utilizes the Model-View-Controller (MVC) architectural pattern to enhance automated grading functionality and ease of maintenance. The main objectives of the system are to simplify the process of administering SQL exams, to make it user-friendly for students to enter their SQL statements, and as a means for teachers to automate the grading process. This allows a clear separation between three separate modules: Model to manage data, View to present the application to users, and Controller to manage the application logic. This separation allows for modular development, easier maintenance, and code reuse. The fundamental aspect of the system lies in its automated grading mechanism, which intelligently compares the SQL queries submitted by students with the corresponding validated answer keys stored in the database. Extensive black-box testing was conducted to ensure the reliability and accuracy of the system with various test cases to assess its ability to assess responses and provide real-time feedback to students, in addition to smooth and intuitive navigation within the system. All testing criteria yielded successful results with 100% agreement proving the robustness of the system with all possible locations that could potentially be used in higher education structures. The system provides a scalable and flexible approach to address the challenges associated with SQL assessment in academic institutions, thereby facilitating uniform, efficient, and objective evaluation standards. The system uses data up to October 2023 to prevent the model from becoming obsolete